(untitled) (Research, Society and Development, 2021)
The Systematization of Nursing Care (SAE) is crucial to providing safe nursing care, as it provides nurses with technical, scientific and human resources, in addition to improving the quality of care provided to the client. Thus, the Intensive Care Unit (ICU) is one of the most complex care units in a hospital. The present study aims to analyze the challenges of the nursing team for the implementation of SAE in ICUs. This is an Integrative Review. To search for publications, the following descriptors were selected: Intensive care unit; Nursing Process; Nursing Services, using the Boolean operator AND for the crossing of descriptors. The search was carried out online in January 2021, in the databases CINAHL, MEDLINE, LILACS e BDENF. After applying the inclusion and exclusion criteria, a final sample of 10 articles was obtained. Two thematic categories were elaborated: "Difficulties experienced by nurses in the process of systematizing care in the ICU" and "Challenges related to structuring the process in the implementation of SAE in the ICUs". Thus, several challenges were identified for the implementation of SAE in ICUs, such as: lack of theoretical knowledge, reduced number of professionals; overload of work, lack of time and poor preparation of the forms. Thus, the introduction of disciplines that include SAE in nursing degrees as well as greater involvement of the hospital institution contribute to the achievement of benefits for the institution and for patients, through the implementation of SAE in a competent and qualified manner.